Crossing the (watershed) divide: satellite data and the changing politics of international river basins. Issue 1 (15th September 2015) - Gleason, Colin J; Hamdan, Ali N
Abstract : Acquiring freshwater resources is a necessary component of sustainable human settlement subject to increasing pressure from population and climate changes. This sometimes scarce resource primarily comes from rivers, and international river basins (IRBs), where watersheds and watercourses cross political boundaries, are often spaces of great political tension and conflict worldwide. Such conflict potential has garnered interest from a wide range of research communities, and each emphasises public access to hydrologic data as integral to successful international management of IRBs. However; these hydrologic data, especially measurements of river flow rate, are often closely guarded state secrets. Satellites have been cited as a key technology set to challenge this data monopoly that have yet been unable to calculate river flow rate without some form of guarded ancillary data. Now, at‐many‐stations hydraulic geometry (AMHG) offers a means of circumventing data limitations without any a priori information, and the forthcoming NASA/CNES Surface Water and Ocean Topography (SWOT) satellite also promises to estimate flow rates solely from its novel measurements following launch. In this paper, we explore how these newly available estimates of river flow rate could reconfigure water‐management and interstate relations in IRBs, and demonstrate AMHG, for two cases: the Ganges–Brahmaputra and Mekong. For these basins we find that satellite flow rate retrievals will likely reinforce and favour state‐level negotiations of water resource governance. Also, satellite flow retrievals can have the direct, concrete effect of improving hydrologic understanding of the upstream Ganges–Brahmaputra, a sorely needed advance that will positively benefit millions of Bangladeshis and affect state‐level interactions between India, China, and Bangladesh. Finally, we avoid offering prescriptive water management solutions for each case, as local stakeholders will ultimately determine if and how such satellite retrievals will be used.